A rare case of a solitary perianal neurofibroma - Kim, Dmitriy; George, Elizabeth; Nalla, Maheshwari; Chirayath, Subin (International Surgery Journal, 2018)
Neurofibromas are benign nerve sheath tumors commonly associated with Neurofibromatosis type 1 (NF1). In patients without the diagnosis of the NF1, these lesions are referred to as solitary neurofibromas. Gastrointestinal involvement is exceedingly rare in NF1 and can manifest in a variety of different ways. This case report involves a 50-year-old hispanic female with an isolated neurofibroma of the perianal region in the absences of any medical or family history of NF1. Since there are very few cases of solitary neurofibromas reported in literature, it is important to document such cases and follow patients with this disease closely given that it can be an initial presentation of NF1 and because of its possible malignant potential.